Climacteric symptoms more severe in 2010 than in 2000 – experience of Finnish women aged 52–56 years not now or previously on menopausal hormone therapy. (December 2021) - Lipasti, Maija; Jalava-Broman, Jaana; Sillanmäki, Lauri; Mäkinen, Juha; Rautava, Päivi
Highlights: Little is known about the cohort effect on the experience of climacteric symptoms. The present study reveals that women aged 52–56 years not now or previously on menopausal hormone therapy experienced more severe climacteric symptoms in 2010 than had a similarly aged cohort in 2000. We did not find any significant associations between sociodemographic or health background and climacteric symptoms. Abstract: Objectives: To analyze and compare the experience of climacteric symptoms and their associations with sociodemographic and health-related characteristics in two cohorts of Finnish women aged 52–56 years, born ten years apart and not now or previously on menopausal hormone therapy (MHT). Study design: Nationwide population-based time-trend study with a large number of participants ( n  = 1986 + 1988). Main outcome measures: The experience of climacteric symptoms was assessed by 12 commonly used menopause-related symptoms. Results: Women aged 52–56 experienced more moderate or severe symptoms and fewer mild symptoms in 2010 than in 2000. Being unemployed or inactive was associated with more severe symptoms ( P   =  0.007), but employment status had no effect on the relative odds estimates. Conclusions: The influence of the birth cohort and time-period effects as well as work-related factors on the experience of climacteric symptoms in women not now or previously on MHT needs further research, particularly since the change in the experience of symptoms found in this study occurred within only ten years.